Limited church unlimited kingdom - Rienow, Rob. (Nashville Randall House Publications, 2013)
"God created the institution of the family and the institution of the local church with distinct purposes. Both exist for the glory of God and the spreading of the Gospel. Limited Church: Unlimited Kingdom seeks to reclaim the simple, transformational, and global mission revealed in Scripture for both the church and family. Rob Rienow shares from a heart for ministry and gives significant insight based on his ministry experience as well as the experiences of others. His motivation for writing is to see churches and families have a lasting impact on future generations" -- Publisher description.
Section One. The sufficiency of Scripture -- 1. The battle of the century -- 2. Everything important -- 3. Every good work -- 4. A dangerous doctrine -- Section Two. The lost doctrine of jurisdiction -- 5. Jurisdiction 101 -- 6. When more is less -- Section three. God's mission for the local church -- 7. The worship of God -- 8. Preaching the Bible -- 9. Equipping and caring in the church -- 10. Shepherding in the church -- Section four. God's mission for the family -- 11. Family ministry in the torah -- 12. Family ministry in the Old Testament -- 13. Family ministry in the Gospels (Part 1) -- 14. Family ministry in the Gospels (Part 2) -- 15. Family Ministry in the New Testament -- 16. Family ministry through church history -- Section five. Uniting church and family in the Great Commission -- 17. Caring for the poor -- 18. Transforming youth and children's ministry -- 19. Leading change -- 20. Children in church -- 21. Building marriages and multiplying your church -- 22. Elevating singles ministry -- 23. Discipling men and women -- 24. Accelerating evangelism -- 25. Every thought for the Gospel
Includes bibliographical references.
Keywords: Church; Families -- Biblical teaching; Families -- Religious life; Families; Kingdom of God